MANUSIA DAN LINGKUNGAN DALAM NOVEL LIFE IN THE IRON MILLS KARYA REBECCA HARDINGS DAVIS - Juliasih K (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to investigate the possibilities of alleviating the damage of the environment as a result of industrialization driven by the capitalist system as seen in Life in the Iron Mills, a novella by Rebecca Harding Davis. This study applied ecocriticism which succinctly might be defined as study of the relation between literature and environment conducted in a commitment to environmental praxis. The findings show that there should be the actions of moral principles as a consideration in social policies, politics, and economy. The principles include respect, responsibility, love and care, simplicity, and justice. These actions allow changes from the material-oriented lifestyle to the simple lifestyle and are done by an individual or community to encourage the reform. Everybody should jointly and actively practice the environmental ethics.